2014
DOI: 10.1161/circulationaha.114.011677
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation Watershed

Abstract: A 55-year-old, previously healthy man was admitted to another hospital with deep-venous thrombosis in both legs and massive pulmonary embolism verified by chest computed tomography (CT). He presented with severe dyspnea and hypotension refractory to inotropes. Fibrinolytic therapy with recombinant tissue plasminogen activator was initiated, but the patient further deteriorated and required cardiopulmonary resuscitation for a period of 30 minutes. After return of spontaneous circulation, he remained in cardioge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 2 publications
1
62
0
Order By: Relevance
“…Multiple studies have shown that coronary perfusion worsens, especially if the patient is cannulated peripherally. Because relative cerebral or coronary hypoxia occurs in many situations due to a "watershed" effect, it is imperative to check blood saturations at multiple sites to determine if perfusion is adequate everywhere to avoid to misdiagnose the "Harlequin syndrome" due to inadequate mixing of the two parallel circulations (ECMO and native heart) [23,54,55].…”
Section: Iabp During Ecmomentioning
confidence: 99%
“…Multiple studies have shown that coronary perfusion worsens, especially if the patient is cannulated peripherally. Because relative cerebral or coronary hypoxia occurs in many situations due to a "watershed" effect, it is imperative to check blood saturations at multiple sites to determine if perfusion is adequate everywhere to avoid to misdiagnose the "Harlequin syndrome" due to inadequate mixing of the two parallel circulations (ECMO and native heart) [23,54,55].…”
Section: Iabp During Ecmomentioning
confidence: 99%
“…As such, vasopressor dosing and volume supplementation have to be carefully adjusted during VA-ECMO. VA-ECMO has successfully been used in various conditions such as post-cardiotomy cardiogenic shock [26], shock caused by myocardial infarction [27], decompensated non-ischemic heart failure [28], fulminant myocarditis [29,30], or pulmonary embolism prior to embolectomy [31,32] in all of the aforementioned cases in a bridge-to-recovery strategy. As with VV-ECMO, VA-ECMO has successfully been used in awake patients avoiding mechanical ventilation [33].…”
Section: Veno-arterial Cannulation (Va)mentioning
confidence: 99%
“…One of the most important issues is the so-called watershed phenomenon, i.e., an artificial competition zone between antegrade blood flow from the heart and retrograde blood flow from the ECMO [6,31,44]. It is located at a region somewhere between the ascending aorta and the thoracic aorta at the diaphragm level in most cases, and varies over time [44] and between individual patients.…”
Section: Veno-arterial Cannulation (Va)mentioning
confidence: 99%
“…In bifemoral venoarterial extracorporeal membrane oxygenation (VA ECMO), the transition point at which the antegrade pulsatile output from the left ventricle and the retrograde non-pulsatile ECMO output collide is referred to as watershed [1]. Currently, no standard method is available to determine its location.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, no standard method is available to determine its location. Occasionally, contrast-enhanced computed tomography (CT) or angiography has been used [1][2][3]. Both techniques, however, bear disadvantages including radiation exposure and use of iodinated contrast media.…”
Section: Introductionmentioning
confidence: 99%